EFFECT OF CORPORATE SOCIAL RESPONSIBILITY TO FINANCIAL PERFORMANCE OF BANKING COMPANIES - Hendra, Krisphus Chrestian; Herawati, Tubandrijah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research isaimedtoobtain empirical evidance the influence of corporate social responsibility activities to financial performance on banking companies. Return On Assets (ROA), Return On Equity (ROE) and Net Interst Margin (NIM) are used as the proxy of financial performance. Public banking companies which are listed in Indonesia Stock Exchange year 2009-2012 and doing the corporate sosial responsibility disclosure in annual report by successive that produce 14 each year samplesis usedas an object ofresearch. Samples in this research are determined by purposive sampling method. The research data is analyzed by using multiple linear regression. The result showsthatcorporate social responsibility has effect onROA, ROE, and NIM. More and more corporate social responsibility disclosure in the annual report will increasingly affect the company financial performance Key Words : Corporate Social Responsibility, Financial Performance, ROA, ROE, NIM